The Implementation of the Schoolwide Enrichment Model in Italian Schools - Milan, Lara; Reis, Sally M. (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2020)
In this article, we describe the results of a research study investigating the effects of a programming model specifically designed to apply the pedagogy of gifted education to the overall process of schoolwide enrichment, The Schoolwide Enrichment Model (SEM, Renzulli & Reis, 2014). The specific factors examined during the implementation included student attitudes toward learning, teacher attitudes toward teaching, students’ creative productivity, and the processes involved in the implementation of SEM. The study also investigates SEM adaptability to the Italian education system as the first pilot project implementing The Schoolwide Enrichment Model in Italian public schools. Positive changes were found in both student and teacher attitudes toward educational approaches to talent development, and more favorable attitudes toward special programming on the part of parents were also noted, suggesting new and more positive perspectives about gifted education and talent development in Italy.